Measurement of the difference in the geomagnetic induction between the magnetometer pillars of the geomagnetic observatory of the Ukrainian Antarctic Akademik Vernadsky station - M. Leonov; Yu. Otruba (Ukrainian Antarctic Journal, 2021)
The article describes the features of measurements of spatial inhomogeneities of the geomagnetic field between the pillars of magnetometers in the measuring pavilion, which were carried out at the geomagnetic observatory of the Ukrainian Antarctic Akademik Vernadsky station in 2015. Some preliminary results of these measurements are also given. The concept of the timescaled value of the geomagnetic field induction is introduced, which is convenient for compensating for time changes of the real geomagnetic induction and bringing it to one reference level of induction. The differences in geomagnetic induction between pillars are obtained as the differences in time-scaled values of the geomagnetic induction on the pillars. The technique allows comparing long-term series of measurements of field inhomogeneities at important points in space. The main objectives are to increase the accuracy of measurements of local inhomogeneities of the geomagnetic field in the measuring pavilion of the geomagnetic observatory of the Ukrainian Antarctic Akademik Vernadsky station and to determine the differences in the geomagnetic induction between the pillars on which the magnetometer sensors are installed. Obtaining numerical values of the differences in the geomagnetic induction between the pillars as objective criteria needed to assess the accuracy of the data in the final processing of geomagnetic observatory data. The method of comparison of two series of data is used: one obtained by the scalar magnetometer installed in the observatory as a mandatory stationary device, and the other obtained during measurements with a mobile magnetometer at the desired points in space. Compensation of temporal changes of the geomagnetic field by time-scaling the measurement readings of the mobile magnetometer relative to one reference value and thus, bringing them to one selected and fixed time epoch. Special geometric scheme of mobile measurements in the space around the pillars with magnetometer sensors or at important points in space. A rough estimate of method errors. Based on the analysis of the obtained data, the efficiency of the method and its acceptable potential accuracy were confirmed. We obtained approximate numerical values of the differences in the geomagnetic fieldinduction between the pillars on which the magnetometer sensors are installed. Further increase in the accuracy of determining these differences is possible using modern devices of high accuracy and GPS-synchronization of mobile measurements.